National culture and the preference for management controls: An exploratory study of the firm—Labor market interface - Chow, Chee W.; Kato, Yutaka; Shields, Michael D. (Accounting, Organizations and Society, 1994)
This study uses Hofstede's taxonomy of work-related national cultural dimensions to analyze preferences for specific management controls at the interface between the organization and the external labor market. Four experiments were conducted with samples of last-semester Japanese and U.S. MBA students. Most of the results did not provide support for the four hypotheses. These findings are used as the basis for suggesting potential directions for future empirical refinements and theory construction.